Atypical Kawasaki disease presenting with macroscopic hematuria in an infant: a case report - V. Thadchanamoorthy; Kavinda Dayasiri; I. R. Ragunathan (Journal of Medical Case Reports, 2023)
Abstract Background Kawasaki disease is an acute febrile condition in children. It affects mainly children under 5 years old, and is known to cause coronary artery abnormalities if treatment is delayed. The diagnosis rests mainly on clinical criteria. However, it is also known that some infants do not have diagnostic criteria sufficient enough for the diagnosis of Kawasaki disease. Further, children may rarely present with unusual features, and this entity is recognized as “Atypical Kawasaki disease.” Case presentation We present the case of a 9-month-old Tamil boy who presented with sterile gross hematuria in association with prolonged fever, lymphadenopathy, and generalized maculopapular rash. He had high inflammatory markers and echocardiogram disclosed left coronary artery dilatation. The diagnosis of incomplete Kawasaki disease was confirmed based on clinical grounds supported by investigations and exclusion of differential diagnosis. The child showed a good response to intravenous immunoglobulin and aspirin. Conclusion Kawasaki disease is one of the important differential diagnoses of protracted fever of unknown origin in very young children. Since delayed treatment is associated with a high risk of complications, atypical Kawasaki disease needs to be suspected in children presenting with unusual features such as macroscopic hematuria that occurs in association with unexplained prolonged fever.